Forced Convection and MHD Effect of Non-Newtonian Fluids Along a Pipe - Moslemi, Mehdi (Mechanical Technology and Engineering Insights, 2025)
In this paper, the forced convection heat transfer of incompressible, Power law Non-Newtonian fluids through two-dimensional circular pipes in the presence of an external uniform magnetic field was considered. Moreover, momentum and energy equations are solved using a finite volume method and a simple algorithm. Two cases of the thermal boundary condition, a constant temperature and a constant heat flux at the wall, are investigated. The viscous and Joule dissipations are taken into account in the energy equation. Moreover, the influence of the magnetic field and flow behavior index (n) on the velocity distribution, the friction factor, and the Nusselt numbers is discussed. Also, the influence of the viscous and Joule dissipations on the Nusselt numbers is investigated. The results show that the magnetic field has a damping effect on the flow for all values of n. By increasing n, the maximum fluid velocity and friction factor will increase. Increasing n increases maximum fluid velocity and friction factor. Increasing the Hartmann number decreases maximum fluid velocity and increases the friction factor. Also, the increment in the Brinkman number decreases the value of the Nusselt number for all Hartmann numbers and n.